Norms, Norm Sets, and Reference Groups: Implications for Household Interest in Energy Technologies - Christine Horne; Thomas Familia (Socius, 2021)
Household adoption of rooftop solar panels and battery storage can potentially reduce the negative environmental impacts of the electric grid. We argue that the number of socially close (friends and family) and geographically close (neighbors) others who have rooftop solar panels will affect norm expectations regarding how much others approve of solar panels and battery storage and expectations about how personally beneficial those technologies are likely to be. We test our hypotheses using survey data collected from California homeowners and find partial support. We find evidence for the significance of socially close others (rather than neighbors), highlighting the importance of identifying the appropriate reference groups when studying norms. Our results also provide insight into how one category of behavior (adoption of solar panels) can influence norm expectations about another less visible behavior (battery storage), suggesting a mechanism that may contribute to norms regulating private behaviors.